Loss of Diacylglycerol Kinase α Enhances Macrophage Responsiveness - Manigat, Laryssa C.; Granade, Mitchell E.; Taori, Suchet; Miller, Charlotte Anne; Vass, Luke R.; Zhong, Xiao-Ping; Harris, Thurl E.; Purow, Benjamin W. (Frontiers in Immunology, 2021)
The diacylglycerol kinases (DGKs) are a family of enzymes responsible for the conversion of diacylglycerol (DAG) to phosphatidic acid (PA). In addition to their primary function in lipid metabolism, DGKs have recently been identified as potential therapeutic targets in multiple cancers, including glioblastoma (GBM) and melanoma. Aside from its tumorigenic properties, DGKα is also a known promoter of T-cell anergy, supporting a role as a recently-recognized T cell checkpoint. In fact, the only significant phenotype previously observed in Dgka knockout (KO) mice is the enhancement of T-cell activity. Herein we reveal a novel, macrophage-specific, immune-regulatory function of DGKα. In bone marrow-derived macrophages (BMDMs) cultured from wild-type (WT) and KO mice, we observed increased responsiveness of KO macrophages to diverse stimuli that yield different phenotypes, including LPS, IL-4, and the chemoattractant MCP-1. Knockdown (KD) of Dgka in a murine macrophage cell line resulted in similar increased responsiveness. Demonstrating in vivo relevance, we observed significantly smaller wounds in Dgka-/- mice with full-thickness cutaneous burns, a complex wound healing process in which macrophages play a key role. The burned area also demonstrated increased numbers of macrophages. In a cortical stab wound model, Dgka-/- brains show increased Iba1+ cell numbers at the needle track versus that in WT brains. Taken together, these findings identify a novel immune-regulatory checkpoint function of DGKα in macrophages with potential implications for wound healing, cancer therapy, and other settings.